Resilience in institucionalized adolescences. A Gestalt play therapy intervention - Pacheco Patrón, Abril (Consorcio de Universidades Mexicanas A.C., 2017)
The objective of this study is to know if an intervention program in Gestalt play therapy, favors the capacity of resilience in institutionalized adolescents. The sample consisted of three participants, males, aged between 13 and 16 years. The instrument used in the pre and post-test was the Resilience Questionnaire (strength and personal security) of González Arratia et al. (2008), which consists of 30 reagents. The intervention program consisted of 20 sessions lasting approximately 45 minutes. Individually interpreted results indicate that resilience levels increased after intervention on all factors, however, the increase in resilience was not statistically significant. Results are discussed in terms of sample size; It can ́t be concluded that Gestalt play therapy contributes to strengthening resilience for this sample of adolescents.